Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/bcpt.13005
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Acute Aluminium Phosphide Poisoning: A Risk‐Prediction Nomogram Approach

Abstract: Aluminium phosphide (AlP) is a toxic agent associated with a high mortality rate following acute exposure from various routes. The aim of this study was to determine the clinical and laboratory findings useful for predicting the medical outcome of AlP-poisoned patients using established scoring systems. This is a prospective study of AlP-poisoned patients from 2010 to 2015 in Ardabil, Iran. All patients that presented with a confirmed diagnosis of acute AlP poisoning in the study interval were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 41 publications
(51 reference statements)
0
40
0
Order By: Relevance
“…Recently, Farzaneh et al proposed a risk prediction nomogram approach based on a group of similar clinical and biochemical variables, i.e., SBP, GCS score, bicarbonate level, and urine output. 22 However, the relatively larger sample size in our study allows for greater accuracy in determining the relative importance of mortality parameters.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Farzaneh et al proposed a risk prediction nomogram approach based on a group of similar clinical and biochemical variables, i.e., SBP, GCS score, bicarbonate level, and urine output. 22 However, the relatively larger sample size in our study allows for greater accuracy in determining the relative importance of mortality parameters.…”
Section: Discussionmentioning
confidence: 96%
“…Most recently, poisoning with AlP is the cause of many poisoning-related deaths in Iran for which no antidotes have yet been reported [ 24 , 25 ]. Mortality rate from AlP poisoning is even high in the ICU patients, and in some studies, it has been reported to be 75–100% [ 26 ]. In our study, two (0.7%) cases of AlP poisoning, both severe cases, were recorded but improved by means of certain treatments including intra-aortic balloon pump insertion.…”
Section: Discussionmentioning
confidence: 99%
“…El-Sarnagawy (2017) reported alike results. Farzaneh et al (2018) reported insignificant lowering in K level in non-survivors. Hypokalemia after metal phosphides toxicity may be due to vomiting.…”
Section: Discussionmentioning
confidence: 93%